Difficulties in Emotion Regulation, Alexithymia, and Social Phobia Are Associated With Disordered Eating in Male and Female Undergraduate Athletes - Benau, Erik M.; Wiatrowski, Ryan; Timko, C. Alix (Frontiers in Psychology, 2020)
IInvestigations of disordered eating in the athlete population tend to focus on females and the influence of sport level. This leaves unanswered whether, and how, team interdependence (i.e., whether the competition is engaged with one person or as a team) may differentially impact male athletes. In the present study, we recruited a sample of non-athletes, individual athletes, and team athletes and examined the interaction of gender and teammate interdependence on established psychosocial risk factors for disordered eating, including social phobia, alexithymia, and emotion regulation. Although we identified a significant main effect of gender, there was no main effect of team type, nor was there a significant interaction of gender and team type. Using descriptive discriminant analysis (DDA), these variables significantly discriminated between genders. Women were defined by higher scores than men on drive for thinness, body dissatisfaction, and emotion recognition and men were defined by relatively higher scores on emotion dysregulation and binge eating. When we combined all athletes and compared them with non-athletes, a significant interaction of gender and athlete status emerged such that female athletes, compared to male athletes and women non-athletes, were defined by higher scores on drive for thinness, emotion dysregulation, and binge eating. Conversely, male athletes, compared to female athletes, were defined by greater difficulty identifying feelings and body dissatisfaction. Non-athletes were not well defined by the discriminant function. These results highlight that emotional processes convey risk for eating disorders in men and women, particularly in athletes, and these risk factors are not uniform.